Determinants of international students' migration intentions for higher education abroad - Hossain, Rashed; Hasan, Md. Hasibul; Uddin, Sayim; Yousuf, Sharjil Bin; Bhuiyan, Mohammad Rakibul Islam (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the determinants of Bangladeshi students' migration intentions for pursuing higher education abroad, with a particular focus on the mediating roles of higher education and job adaptation. The research also explores the moderating influence of socioeconomic status. A quantitative approach was used, involving an online survey of 500 Bangladeshi students, with 325 valid responses analyzed through PLS-SEM and SPSS. Key findings indicate that research opportunities and societal expectations are significant motivators for migration, while socioeconomic status influences migration intentions but does not significantly alter the relationship between higher education and migration. Political instability increases the importance of job adaptation, further enhancing students' intentions to migrate. The study highlights the need for universities, especially in developing countries, to improve research facilities and address social pressures faced by students. Additionally, policymakers are encouraged to mitigate political instability and provide pathways for international students to successfully integrate into foreign job markets post-graduation. This research offers novel insights by incorporating political instability and job adaptation as mediators, contributing to a broader understanding of the academic, social, political, and economic factors influencing migration intentions.